Metropolitan tragedy : genre, justice, and the city in early modern England - Greenberg, Marissa, 1976- (University of Toronto Press, 2015)
Breaking new ground in the study of tragedy, early modern theatre, and literary London, Metropolitan Tragedy demonstrates that early modern tragedy emerged from the juncture of radical changes in London's urban fabric and the city's judicial procedures.